Study protocol: Clinical yarning, a communication training program for clinicians supporting aboriginal and Torres Strait Islander patients with persistent pain: A multicentre intervention feasibility study using mixed methods - Christina M. Bernardes; Ivan Lin; Stephen Birch; Renata Meuter; Andrew Claus; Matthew Bryant; Jermaine Isua; Paul Gray; Joseph P. Kluver; Stuart Ekberg; Gregory Pratt (Elsevier, 2022)
Objectives: Ineffective communication between healthcare clinicians and Aboriginal and Torres Strait Islander patients with persistent pain is a significant barrier to optimal pain management. This manuscript is a study protocol and describes the development and evaluation methods of a tailored, culturally-informed training program, to improve clinicians' communication with patients. Study design: This is a single-arm, multicentre (2 metropolitan and 1 regional persistent pain service) intervention feasibility study that will be evaluated using mixed methods. Methods: A communication training program will be developed informed by qualitative interviews with key stakeholders, and adapt the patient-centred 'clinical yarning' framework for the Queensland context. Evaluation of the effectiveness of the training will involve the analysis of quantitative data collected at three study sites over a 12-month period. At the patient level, communication experience will be rated at differing times of the training rollout to reflect participants' experience of communication either prior to or following the treating clinician attending the communication training. At the clinician level, evaluation of the training program will be based on changes of ratings in the importance of training, knowledge, ability and confidence to communicate with Aboriginal and Torres Strait Islander patients; satisfaction, acceptance and relevance to their clinical practice. This study will be grounded in the needs and preferences of communication of Aboriginal and Torres Strait Islander people living with pain. Conclusion: It is hypothesized that the patient-centred intervention will have immediate benefits for patients, improving patient experience of care. This research will focus on an area of unmet need in addressing persistent pain.